Single visit root canal treatment of a third lower molar with curved canal and Class II disto-occlusal caries: Case report - Tsanie, Maria Latifa; Junaidi, Achmad; Kristanti, Yulita; Nugraheni, Tunjung; Untara, Tri Endra; Santosa, Pribadi; Enggardipta, Raras Ajeng (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2025)
ABSTRACTIntroduction: Root canal treatment (RCT) of mandibular third molars is often considered challenging due to anatomical variability, limited accessibility, and difficulty achieving proper isolation. As a result, extraction is frequently chosen. This case report outlines a successful single-visit RCT on a right mandibular third molar with a curved canal and Class II disto-occlusal caries. Case Report: A 30-year-old female presented with a large cavity on her right lower molar and requested a restorative treatment. Three weeks earlier, devitalization and temporary restoration had been performed by another dentist. Clinical examination revealed no periapical lesion, and percussion testing was negative. Radiographic analysis showed a slight curvature in the distal canal. A pre-curved K-File and the One Curve System were used for instrumentation. The canal was obturated in a single visit, followed by restoration using direct composite and short fiber-reinforced composite. Matrix and PTFE tape were utilized for proper adaptation in the distal area. Conclusion: With accurate diagnosis, understanding of anatomical complexity, and appropriate technique, single-visit RCT on mandibular third molars is achievable. This case supports the viability of conservative treatment for necrotic third molars with asymptomatic apical periodontitis, avoiding unnecessary extraction.Keywords single visit, root canal treatment, third lower molar, curved canal, composite restoration. ABSTRAKPendahuluan: Perawatan saluran akar (RCT) pada molar ketiga mandibula menantang karena variasi konfigurasi saluran, kesulitan akses ke area posterior, dan tantangan dalam isolasi. Akibatnya, pencabutan sering menjadi pilihan. Laporan kasus ini mendeskripsikan protokol RCT kunjungan tunggal pada molar ketiga kanan mandibula dengan saluran melengkung dan karies disto-oklusal kelas II. Laporan Kasus: Seorang wanita 30 tahun datang dengan kavitas besar pada molar ketiga kanan bawah dan menginginkan perawatan tanpa pencabutan. Tiga minggu sebelumnya, dokter lain telah melakukan devitalisasi dan restorasi sementara. Pemeriksaan klinis menunjukkan tidak ada lesi periapikal dan uji perkusi negatif. Radiograf menunjukkan kelengkungan ringan pada saluran distal. RCT dilakukan menggunakan K-file pra-lengkung dengan sistem One Curve. Obturasi dilakukan dalam satu kunjungan, diikuti restorasi komposit langsung yang diperkuat dengan komposit serat pendek. Area distal direstorasi menggunakan matriks dan pita PTFE. Simpulan: RCT kunjungan tunggal pada molar ketiga mandibula dengan pulpa nekrotik dan periodontitis apikal asimptomatik dapat berhasil dilakukan dengan diagnosis akurat dan teknik yang tepat. Pendekatan konservatif ini menunjukkan bahwa pencabutan bukan satu-satunya pilihan.Kata kunci sekali kunjungan, perawatan saluran akar, molar ketiga, saluran melengkung, restorasi komposit.